Digital organizations manufacturing scripts, performativity and semiopolitics - Carmes, Maryse (Information systems, web and pervasive computing series., 2018)
In what sort of assemblages, the strategies and digital policies in organization are made''' Beyond digital mantras and management slogans/fictions, what is the concrete factory of information management system'' What are the parts of the human and no human actors' Is it possible to create a new approach to understand how work change (or not), to explore the potential for a social and cognitive innovation way, considering simultaneously the increase of Data Management and the organizational analytics.